2021
DOI: 10.2196/22916
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Delineation of Media Polarity on COVID-19 Vaccines in Africa: Computational Linguistic Modeling Study

Abstract: Background The global onset of COVID-19 has resulted in substantial public health and socioeconomic impacts. An immediate medical breakthrough is needed. However, parallel to the emergence of the COVID-19 pandemic is the proliferation of information regarding the pandemic, which, if uncontrolled, cannot only mislead the public but also hinder the concerted efforts of relevant stakeholders in mitigating the effect of this pandemic. It is known that media communications can affect public perception a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 67 publications
0
23
0
1
Order By: Relevance
“…Gbashi et al found that most Google news (569) and Twitter posts (637) between February and May 2020 were generally passive to positive towards COVID-19 vaccines in Africa. 50 In contrast, in November and December, Talkwalker media monitoring sentiment analysis from UNICEF found that less than 10% of online posts displayed positive sentiment in 2020. 27,31 Dereje et al in Ethiopia (n= 422) found higher vaccine refusal among participants that primarily receive information from social media (internet) as compared to TV/radio.…”
Section: The Degree Of Community Involvement and Social Norms Influenced Vaccine Acceptancementioning
confidence: 99%
“…Gbashi et al found that most Google news (569) and Twitter posts (637) between February and May 2020 were generally passive to positive towards COVID-19 vaccines in Africa. 50 In contrast, in November and December, Talkwalker media monitoring sentiment analysis from UNICEF found that less than 10% of online posts displayed positive sentiment in 2020. 27,31 Dereje et al in Ethiopia (n= 422) found higher vaccine refusal among participants that primarily receive information from social media (internet) as compared to TV/radio.…”
Section: The Degree Of Community Involvement and Social Norms Influenced Vaccine Acceptancementioning
confidence: 99%
“…Also, several sentiment analysis studies regarding the COVID-19 vaccine have been conducted as of early 2021. A study by Gbashi et al (2021) focused on detecting the opinion of media polarity on COVID-19 vaccine in Africa with Twitter and Google News articles [ 20 ]. Furthermore, additional research investigated public sentiment in India [ 21 , 22 ], Indonesia [ 23 ], and China [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, existing studies have investigated people’s reactions towards COVID-19 vaccines, with a geographical emphasis on the United States [ 14 - 19 ]. Some papers have also studied other countries in the world, including China [ 20 ], South Africa [ 21 ], Australia [ 22 ], the United Kingdom [ 14 , 23 ], Canada [ 24 ], and Africa [ 25 ], and to a global scale [ 26 ]. However, the study period of these works is relatively limited to or predominantly focused on the early stage of the pandemic or up to the end of 2020.…”
Section: Introductionmentioning
confidence: 99%